Forecasting Singapore's electronics trade and production. - Ng, Hui Min. (2008)
In this study on the Singapore electronics industry, four domestic variables, namely retained electronics imports (LRIM), domestic electronics export (LDX), electronics re-exports (LRX) and industrial production (LIP), were linked with global chip sales (LCHIP), in a vector error correction model (VECM). Autoregressive Integrated Moving Average (ARIMA) models were also constructed for the four domestic variables to serve as a benchmark for the evaluation of forecast accuracy. In-sample and out-of-sample forecasts were generated using the recursive estimation method and both classes of models were evaluated based on the root mean square error (RMSE) of their forecasts. The results showed that the VECM model of lag length 2 proved to be better for forecasting LDX and LRX while ARIMA models performed better for LRIM and LIP.